Offline visit intention of online patients: the Grice’s maxims and patient involvement - Cao, Xianye; Liu, Yongmei; Fang, Zian; Zhu, Zhangxiang (BMC medical informatics and decision making, 2025)
Online Healthcare Consulting Services (OHCS) can benefit physicians and patients. However, it is unclear how OHCS and what types of persuasive content enhance patients’ intentions to visit offline. Based on the Elaboration Likelihood Model (ELM) and Grice’s maxims of the Cooperative Principle, we formulated hypotheses related to factors in the central route, peripheral route, and patient involvement that influence patients’ offline visit intentions. We used the amount of information, reliability, relevance, and understandability to measure information quality. By collecting data from an online healthcare site, we employed a regression model to evaluate our hypotheses. The results revealed that central route factors (amount of information, reliability, relevance, and understandability) and peripheral cues positively affect patients’ offline visits. We also verified that patient involvement increases the impact of central route factors. This study extended the application of ELM and Grice’s maxims in the field of OHCS, offering insights into how patients form intentions to visit offline through persuasive online content and providing valuable practical guidance for online physicians.